1993
DOI: 10.1002/app.1993.070480106
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the surface cross‐linking of the high‐density polyethylene induced by plasma treatment on the durability of treatment efficiency

Abstract: SYNOPSISThe structure of the surface cross-linking layer of high-density polyethylene (HDPE) produced by plasma treatment was studied by DSC, X-ray diffraction, elemental analysis, and infrared analysis. The relationship between the cross-linking and the durability of the modification efficiency provided by the plasma treatment was investigated. The results of the structure analysis indicated that the polar groups introduced by the plasma just locate on the upper surface of the cross-linking layer and the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Nitrogen plasma is also effective for surface modification due to formation of nitrogen functionalities such as amino and amido groups [11]. Argon plasma is also used as a pre-treatment for plasma-induced grafting or for cross-linking of molecules in polymer surfaces [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen plasma is also effective for surface modification due to formation of nitrogen functionalities such as amino and amido groups [11]. Argon plasma is also used as a pre-treatment for plasma-induced grafting or for cross-linking of molecules in polymer surfaces [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Argon plasma has been used in many applications, such as pretreatment for plasma‐induced grafting,28–32 crosslinking33, 34 surface macromolecules, removal of contamination on the surface, and ablation of material from the surface to remove a weak boundary layer and increase surface roughness for better adhesion 35. Because argon is an inert gas, it is therefore often used to modify and reorganize the chemical groups that are already present at the surface, rather than to introduce new functional groups to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been observed that argon plasma can introduce oxygen functionality to the surface 36. Argon plasma of polyethylene was shown to incorporate mainly oxygen‐ and nitrogen‐containing surface groups 28, 31, 33, 37. This is due to the reactions between the reactive groups (usually radicals) on the treated surface with components in the air.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, subsurface failure of HDPE is relatively more when HDPE is exposed at the highest power level of 33.75 W, as evident from Figure 25(a), resulting in lowering the joint strength. It has also been observed by other workers that the excessive bond breakage and oxidation are manifested by the formation of low molecular weight oxidized molecules, which deteriorate mechanical properties in the polymer phase, [11,16,21] have also observed that lap shear tensile strength of high density polyethylene to steel and lap shear tensile strength of polypropylene to aluminum increase with increasing duration of exposure until 2 minutes under glow discharge. Then the joint strength saturates with further increasing exposure time.…”
Section: E Fractography Of Surface-modified Polymersmentioning
confidence: 68%
“…Glow discharge under low pressure plasma is a popular technique, which results in better uniformity in surface modification of the polymers. [1,4,16,21] Moreover, it is a dry treatment method, which is better suited for industrial applications. It is now well established that the glow discharge treatment creates physical and chemical changes such as cross-linking, degradation, formation of free radicals, and oxygen functionalization.…”
Section: Introductionmentioning
confidence: 99%